Understanding the grief and loss experiences of carers : research, practitioner and personal perspectives - Jones, Kerry (College teacher); Horne, Joanna (Abingdon, Oxon ; New York, NY : Routledge, 2024)
This book draws on recent research and cutting-edge ideas about bereavement and carers' experiences across the life course to explore carers' experience of loss and discuss their specific needs prior and or following the death of those they care for. Whether care provided is related to a long term or life limiting condition, many carers experience a multitude of losses including indefinite loss characterised by the loss of a taken-for-granted future, and an inability to plan for the future. Carers may also experience anticipatory grief as multiple losses such as companionship, personal freedom, and control manifest. While many carers are dedicated and committed to their role, they are subject to burnout and disenfranchised grief. When the role of caregiver ends as a result of the death of those cared for, this can represent a major change and a period of significant adjustment for carers leading to a range of emotions experienced. This book presents and discusses research findings, practitioner perspectives, and a wealth of personal accounts to illuminate this vital but neglected area and extend our understanding of loss for carers across the life course. This interdisciplinary and interprofessional volume brings together authors from a wide range of backgrounds, including carers themselves. It is an important contribution to the burgeoning literature around the role and experiences of carers and will interest academics, students and practitioners in health and social care, counselling, and psychology with an interest in loss and bereavement.
Keywords: Grief; Loss (Psychology); Caregivers -- Psychology; SOCIAL SCIENCE / Death & Dying; MEDICAL / Caregiving